Maurice Blanchot: 'Theorist' of the Diary?. Issue 2 (July 2022) - Ferguson, Sam
Abstract : Maurice Blanchot's writing on the diary has been presented as ignorant and contemptuous of its object, and as misrepresenting the diary by focusing on its literary qualities. This article rehabilitates Blanchot as a critic and theorist of the diary, and moreover, as a pivotal figure in realising the diary's literary potential. Blanchot's discussion of particular diarists (including Benjamin Constant, Joseph Joubert, Søren Kierkegaard, Franz Kafka, and André Gide), together with his critical reflections, were instrumental in his creation of conceptions of literature that exerted a strong influence on the avant-garde movements of the following decades, even though these avant-gardes rejected the introspective aspect of intimate writings. Furthermore, Blanchot produced a programme for how the diary might become a literary work, which was picked up again by Roland Barthes in 1979, and casts light on experimental uses of the diary in recent decades. Abstract : Les écrits de Maurice Blanchot sur le journal ont été présentés comme ignorants et méprisants à l'égard de son objet, et comme déformant la véritable nature du journal en se concentrant sur ses qualités littéraires. Cet article réhabilite Blanchot en tant que critique et théoricien du journal, et plus encore, en tant que figure centrale dans la prise de conscience du potentiel littéraire du journal. Les discussions de Blanchot sur certains diaristes (notamment Benjamin Constant, Joseph Joubert, Søren Kierkegaard, Franz Kafka et André Gide), ainsi que ses réflexions critiques, ont contribué à la création de conceptions de la littérature qui ont exercé une forte influence sur les mouvements d'avant-garde des décennies suivantes. En outre, Blanchot a réfléchi à la manière dont le journal pourrait devenir une œuvre littéraire précisément par sa recherche du littéraire, ce qui éclaire les utilisations expérimentales du journal au cours des dernières décennies.